Increases in speed do not change gait symmetry or variability in world-class race walkers - Tucker, C. B.; Hanley, B. (Journal of Sports Sciences, 2020)
The aim of this study was to analyse changes in gait variability and symmetry with increasing speed in race walkers. Eighteen international athletes race walked on an instrumented treadmill at speeds of 11, 12, 13 and 14 km·h-1 in a randomised order for 3 min each. Spatiotemporal and ground reaction force data were recorded for 30 s at each speed. Gait variability was measured using median absolute deviation and inter-leg symmetry was measured using the symmetry angle. There was an overall effect of speed on all absolute values except push-off force, but symmetry and variability (except flight time) did not change with increased speed, step length and step frequency. Most athletes were asymmetrical for at least one variable, but none was asymmetrical for more than half of the variables measured. Therefore, being asymmetrical or having higher variability (<5%) in a few variables is normal. Taking all findings together, practitioners should exercise caution when deciding on the need for corrective interventions and should not be concerned that increasing gait speed could increase injury risk through changes to athletes` asymmetry. Race walking coaches should test at competition speeds to ensure that flight times, and any variability or asymmetry, are measured appropriately.